Perlindungan Konsumen Online Dalam Perspektif Maqāṣid al-sharī‘ah: Studi Sosio-Legal di Indonesia: Online Consumer Protection in the Perspective of Maqāṣid al-sharī‘ah: A Socio-Legal Study in Indonesia - Herman, Herman; A Edeth Fuari Anatasya (Sekolah Tinggi Agama Islam Negeri Majene, 2025)
The digital economic transformation has massively expanded online transactions, yet it has also triggered various challenges concerning consumer protection. In this context, maqashid al-shari'ah offers a comprehensive philosophical framework for establishing fair and maslahah-oriented e-commerce regulations. This study aims to examine how the principles of maqashid al-shari'ah can serve as a foundation for formulating consumer protection regulations in online transactions through a socio-legal approach. The method used is normative legal research with a socio-legal approach, analyzing e-commerce regulations in Indonesia and interpreting them based on maqashid values such as hifz al-mal (protection of property), hifz al-nafs (protection of life), and hifz al-'aql (protection of intellect). The findings reveal that regulations based solely on a positivist approach have not optimally safeguarded consumers from risks such as fraud, data theft, and transactional injustices. Integrating maqashid al-shari'ah into e-commerce regulation enriches the protective dimension by embedding values of justice, welfare, and transparency, thereby strengthening consumer trust within the digital ecosystem. This study recommends the formation of regulations grounded in maqashid values and the need for legal reform based on a contextual understanding of the dynamics of digital society to achieve effective and equitable consumer protection.